Seismic characterisation of fault damage in 3D using mechanical and seismic modelling. (November 2016) - Botter, Charlotte; Cardozo, Nestor; Hardy, Stuart; Lecomte, Isabelle; Paton, Gaynor; Escalona, Alejandro
Abstract: Although typically interpreted as 2D surfaces, faults are 3D narrow zones of highly and heterogeneously deformed rocks with petrophysical properties differing from the host rock. Fault zones have been extensively studied in outcrop, but in the subsurface they are barely explored, mainly because they are at the limit of seismic resolution and are rarely drilled and cored. We present a 3D synthetic workflow to assess the potential of seismic data for imaging and characterising fault damage and properties. The workflow is based on forward modelling techniques. First, we run a 3D discrete element model to simulate faulting and associated deformation. Then, we use simple relationships to modify the initial elastic properties of the model based on its volumetric strain. From this reflectivity cube, we apply a ray-based, pre-stack depth migration simulator. Finally, from the resultant seismic image, we use seismic attributes to characterise the fault volume. We illustrate the workflow for a large displacement normal fault in a sandstone-shale sequence for two cases, one with constant fault displacement and another with linearly variable displacement along strike. Seismic cubes of these models for a homogeneous overburden and several wave frequencies are generated. High frequencies show the impact of the fault on the offset and folding of the reflectors. In the variable fault slip model, the fault has less impact as the displacement decreases, and the fault tipline can be interpreted. We extract the fault geobody using three combined seismic attributes: dip, semblance and tensor. The geobody for the constant fault displacement model corresponds to an inner high-deformation area within the fault zone, while in the variable fault slip model the geobody captures better the entire fault zone. Cross plotting of amplitudes and strains shows that the geobody contains all range of strains, but almost all high strain values are within the geobody. This allows a direct comparison between the fault zone identified on the seismic image and that in the mechanical model. Highlights: Discrete element modelling of fault damage Seismic modelling of fault damage Seismic attributes-based fault damage extraction Correlation of seismic amplitude and fault damage Fault damage can be extracted from the seismic image.